Evaluation of Attachment Style and Social Support in Patients With Severe Migraine. Applications in Doctor-Patient Relationships and Treatment Adherence - Belot, Rose-Angélique; Bouteloup, Margaux; Bonnet, Magalie; Parmentier, Anne-Laure; Magnin, Eloi; Mauny, Frédéric; Vuillier, Fabrice (Frontiers in Neurology, 2021)
Objectives:The aim of this observational study was to describe social support and patterns of attachment among patients with migraine. We hypothesised that in comparison to the general population, insecure attachment is overrepresented in migraine patients, and that these patients have less social support. We also aimed to study the specific relationship between attachment and social support. We hypothesized that patients with an insecure attachment style have less social support than patients with a secure attachment style. Methods:A total of 101 consecutive patients (88.1% women) aged between 25 and 60 (average age = 41.4) were recruited at the Specialised Centre for the Consultation of Primary Headaches at the Regional University Hospital Centre of Besançon (France). Migraine impact and disability were evaluated using the Headache Impact Test (HIT-6) questionnaire and Migraine Disability Assessment (MIDAS) questionnaire. Patients also completed several self-administered psychological questionnaires in their validated French versions: the Medical Outcome Survey 36-Item Short-Form Health Survey, the Cungi Scale, the State-Trait Anxiety Inventory, the Beck Depression Inventory, the Relationship Scales Questionnaire and the Sarason’s Social Support Questionnaire. Results:The distribution of attachment profiles was different from that of the general population, with an overrepresentation of insecure attachment styles (p = .018). Our study showed that migraine patients had less social support than the general population, both in terms of the number of people providing support (p = .002) and the level of satisfaction concerning this social support (p = .000). We also found that neither the number of available persons score nor the satisfaction score were statistically different between the four attachment categories (p = .49). Patient’s attachment style and social support influence the patient-doctor relationship, the therapeutic alliance and health behaviours such as treatment adherence. Conclusions:Based on the data we obtained, we developed applications in patient care for people with particular attachment styles and low social support. A treatment plan adapted to the patient's attachment profile should be created to develop "precision medicine" using a personalised approach to the doctor-patient relationship. We would also recommend encouraging patients to participate in support groups, in order to strengthen their attachment systems and gain social support.